The challenge of expanding secondary education and training in Madagascar. (World Bank working paper ;, 2008)
This report, produced with the help of Madagascar's national education team in 2006-07, is designed to contribute to ongoing education reform discussions. It analyzes the constraints to system expansion and presents possible next steps for an appropriate course of action. This report aims to encourage discussion among policymakers, stakeholders and donors, and does not promote one approach over another. To promote a more competitive economy in Madagascar in the 21st century, the government expects to increase the average years of schooling from the current 4.5 years to about 9-10 years by 2015.